Bright NUV mechanofluorescence from a terpyridine-based pure organic crystal. Issue 1 (6th December 2017) - Sun, Qikun; Tang, Liangliang; Zhang, Zhenzhen; Zhang, Kai; Xie, Zongliang; Chi, Zhenguo; Zhang, Haichang; Yang, Wenjun
Abstract : Bright NUV mechanofluorescence from a terpyridine-based pure organic crystal with non-centrosymmetric packing and a piezoelectric space group. Abstract : A bright NUV mechanofluorescent terpyridine-based material with a piezoelectric space group was obtained. The single crystal analysis and quantum chemical calculations indicated the existence of enhanced intermolecular and intramolecular interactions and intersystem crossing, but which did not facilitate the room temperature phosphorescence.